2017
DOI: 10.1111/zph.12370
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 influenza A virus infection associated with respiratory signs in sloth bears (Melursus ursinus)

Abstract: In 2009, a pandemic influenza A virus (pH1N1) spread globally in humans and infected a broad range of captive animals with close human contact. In February 2014, a pH1N1 virus was isolated from a sloth bear with respiratory signs at a US zoo, demonstrating that recurring epidemics present an ongoing threat to animals, including threatened species. This is the first report of pH1N1 infection in sloth bears. To understand the sloth bear virus within the global context of pH1N1, phylogenetic trees were inferred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…pdm09 are maintained at protective levels (greater than or equal to 32HI) for up to 15 months after a single influenza infection (Sridhar et al, 2015). Although we could not rule out the possibility that the cheetahs were pre-exposed to the virus, our findings showed that cheetahs naturally infected with influenza virus maintained detectable levels of antibodies for at least 10 months ( Table 2) pdm09 virus infection has been reported in a variety of captive wild animals including threatened species such as giant pandas (VU) (Li, Zhu, et al, 2014;Martelli et al, 2019), a sloth bear (Melursus ursinus) (VU) (Boedeker et al, 2017) and a black-footed ferret (Mustela nigripes) (endangered animal, EN) (Schrenzel et al, 2011). More recently, serological evidence of influenza virus infection was found in tigers (EN) and…”
Section: Discussionmentioning
confidence: 76%
“…pdm09 are maintained at protective levels (greater than or equal to 32HI) for up to 15 months after a single influenza infection (Sridhar et al, 2015). Although we could not rule out the possibility that the cheetahs were pre-exposed to the virus, our findings showed that cheetahs naturally infected with influenza virus maintained detectable levels of antibodies for at least 10 months ( Table 2) pdm09 virus infection has been reported in a variety of captive wild animals including threatened species such as giant pandas (VU) (Li, Zhu, et al, 2014;Martelli et al, 2019), a sloth bear (Melursus ursinus) (VU) (Boedeker et al, 2017) and a black-footed ferret (Mustela nigripes) (endangered animal, EN) (Schrenzel et al, 2011). More recently, serological evidence of influenza virus infection was found in tigers (EN) and…”
Section: Discussionmentioning
confidence: 76%
“…Our findings indicate that the influenza virus in giant pandas was most likely directly or indirectly from humans with seasonal influenza. Of interest, respiratory infection in a sloth bear due to pH1N1 has also been observed in a zoo in the United States in 2014, indicating that pH1N1 can probably infect a variety of bears ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse zoonosis was also proposed as the source of infection for five sloth bears ( Melursus ursinus ) at the Smithsonian National Zoo in Washington DC, which, in February 2014, developed nasal discharge, coughing and sneezing one month subsequent to several caretakers contracting influenza‐like illness (Bodeker et al, ). Nasal samples from one bear revealed a strain of A(H1N1)pdm09 closely related to one circulating widely in humans during the concurrent flu season (Bodeker et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse zoonosis was also proposed as the source of infection for five sloth bears ( Melursus ursinus ) at the Smithsonian National Zoo in Washington DC, which, in February 2014, developed nasal discharge, coughing and sneezing one month subsequent to several caretakers contracting influenza‐like illness (Bodeker et al, ). Nasal samples from one bear revealed a strain of A(H1N1)pdm09 closely related to one circulating widely in humans during the concurrent flu season (Bodeker et al, ). Compared to captive species, identifying reverse zoonosis in synanthropes is more challenging due to our lack of knowledge regarding the existence of an influenza A reservoir, the extent and causes of morbidity and mortality during flu season and whether prior contact with humans occurred.…”
Section: Discussionmentioning
confidence: 99%